Correction osteotomy for bilateral varus knee deformity caused by premature epiphyseal closure induced by hypervitaminosis A: a case report - Masatake Matsuoka; Tomohiro Onodera; Tokifumi Majima; Koji Iwasaki; Daisuke Takahashi; Eiji Kondo; Norimasa Iwasaki (BMC Musculoskeletal Disorders, 2019)
Abstract Background A vitamin A derivative, 13-cis-retinoic acid (isotretinoin), has been administered to treat several types of pediatric cancer and has improved survival rates in patients despite being known to induce premature epiphyseal closure. As the number of patients treated by 13-cis-retinoic acid increases, demands for salvage treatment after systemic retinoid therapy are emerging. However, few studies have described the surgical treatment of this disease. Case presentation We report a case with bilateral varus knee deformity due to premature epiphyseal closure that occurred during treatment with isotretinoin for neuroblastoma. The patient was successfully treated with correction osteotomy using a Taylor spatial frame in the right knee joint and femoral closed wedge osteotomy using a locking plate in left knee joint. Histopathological examination of the growth plate showed polar irregularity of chondrocytes and decreased cartilage matrix without apoptosis. In contrast, arthroscopic findings showed an intact joint surface. No recurrence of varus deformity was evident on follow-up at 1 year. Conclusions To the best of our knowledge, this represents the first report of correction osteotomy for varus knee deformity due to premature epiphyseal closure that occurred during treatment with isotretinoin.